IKEA Effect vs. Trophy Effect - An Experimental Comparison - Christoph Bühren; Marco Pleßner (Philipps-University Marburg, School of Business and Economics, 2020)
Successful work – either invested to create or to obtain a product – increases the customer's valuation of the product. These phenomena are called the IKEA and the trophy effect. We test both of them separately as well as combined and find that the trophy winner effect looms larger than the IKEA effect for inexpensive items, in our case paper planes. For more expensive products, in our case 3-D-puzzles, we find a trophy loser effect. Positive emotions of trophy winners drive our result for inexpensive products, whereas negative emotions of trophy losers drive our result for more expensive products. We discuss the implications of our findings.
Keywords: 330; effort; labor; competition; achievement; failure; valuation